Behavioural flexibility in Lumbricus terrestris burrowing - Butt, Kevin R.; Nuutinen, Visa (Elsevier, 2024)
Lumbricus terrestris is an epi-anecic earthworm, normally occupying a 1–2 m deep, vertical burrow. Some observations suggest that population persistence in much shallower burrows could be possible in a mild and humid climate. This was further investigated at an ex-industrial site in NW England, with a topsoil less than 0.15 m deep, above inert subsoil formed from semi-weathered Leblanc waste. L. terrestris were collected from an adjacent woodland soil and introduced into unoccupied areas. After four days, settlement and survival were studied by targeted sampling of half of the individuals, and depth of burrows were measured by resin casting. After 14 months, the second half of inoculated areas were studied and after another four years a further general survey occurred. After four days, 41 % of targeted worms were recovered, with 0.11 m mean burrow depth and burrows ending at the subsoil interface. After 14 months, all age classes of L. terrestris were present and burrow depth had not changed. After five years, adult, juvenile and hatchling L. terrestris were present, demonstrating establishment of a breeding population. In a parallel laboratory experiment, with site topsoil and subsoil in Evans’ boxes, L. terrestris avoided subsoil and constructed U-shaped burrows. The results show that through flexible burrow construction, L. terrestris can survive above highly constraining subsoil conditions. This is likely to be only possible where severe droughts are uncommon, and topsoil does not freeze in winter.
Keywords: lierot; käyttäytyminen; maaperäeläimistö; maaperäfysiikka; sopeutuminen; Epi-anecic earthworms; Behavioural flexibility; Subsoil conditions; Leblanc waste